L'ETÀ EOCENE MEDIO - OLIGOCENE INFERIORE DELLE MARNE Dl MONTE PIANO NELLA SINCLINALE Dl VIANO (PROV. REGGIO E., APPENNINO SETTENTRIONALE) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
The micropaleontological study (Foraminifera) of the upper part of the Monte Piano Marls up to the transition to the overlying Ranzano Sandstones has pointed out the presence of Middle Eocene and Lower Oligocene microfaunas.Species attributable to Zone P 15 and/or to the earlier part of P 16 (Late Eocene) are usually reworked in sediments of the latest Eocene—Early Oligocene age.The reworking of planktonic and benthonic faunas can be related to resedimentation phenomena, which are also evidentiated by sedimentological features and thanatocoenosis characters.The composition of the benthonic foraminiferal faunas indicates a Iower bathyal—abyssal environment; displaced species from shallower depths are not present.These data suggest that, during the latest Eocene—Early Oligocene, the Monte Piano Marls basin was affected by differential uplifts with the formation of structural highs and their subsequent erosion.
Keywords: Monte Piano Marls; Biostratigraphy; Middle Eocene—Early Oligocene; Northern Apennine.